2013 Fourth International Conference on Computing, Communications and Networking Technologies (ICCCNT) 2013
DOI: 10.1109/icccnt.2013.6726693
|View full text |Cite
|
Sign up to set email alerts
|

Automated techniques and tools for program analysis: Survey

Abstract: Dealing with program analysis for software development and the understanding of source code of software exhibit many research possibilities. The field of program analysis scrutinizes the approaches and techniques to analyze the properties of program including its analysis, flow, program development, algorithm, reverse engineering and other invisible features.The goal is to improve our understanding of inherently invisible and intangible software, particularly when dealing with large information spaces that cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Instrument. Lots of researches [24,25] have indicated that program instrumentation plays a very important role in program analysis. Program instrumentation can be used to memory access analysis [26], program behavior analysis [27], data structure recovery [28], and vulnerability mining [22], etc.…”
Section: Expanding the Usage Of Staticmentioning
confidence: 99%
“…Instrument. Lots of researches [24,25] have indicated that program instrumentation plays a very important role in program analysis. Program instrumentation can be used to memory access analysis [26], program behavior analysis [27], data structure recovery [28], and vulnerability mining [22], etc.…”
Section: Expanding the Usage Of Staticmentioning
confidence: 99%
“…From an epistemic perspective, the implementation of a specified model on a computer requires a researcher to argue that the simulation model is an error free and correct software implementation of the simulation model specification on the given physical hardware. A formal, algorithmic code verification is often not feasible for complex software (D 'Silva et al 2008;Ashish and Aghav 2013).…”
Section: Implementing (3)mentioning
confidence: 99%